KAJIAN MAQASHID AL-SHARI'AH TERHADAP NILAI-NILAI ISLAMI PADA SEBUAH TRANSAKSI - Muhammad Zainuddin Sunarto; Putri Nur Afrida; Ulfia Nuriantini (Fakultas Agama Islam Universitas Nurul Jadid, 2022)
All forms of muamalah can be done unless evidence forbids it. In Islam, lending and borrowing are not prohibited. Even people who give debts or loans to other people who are in dire need are something that is liked or recommended because in it there is a great reward. The reality in society is that the financial transactions carried out are not by sharia values; this is evidenced by the absence of elements that must be found in the transaction, such as contracts and clarity of the price of goods. Most Indonesian occupation adherents of the Syafii madhhab, which in the sharia fiqh discourse, all transactions carried out must be based on a clear contract. Apart from that, the public has not been adequately educated regarding the urgency of sharia transactions in each economic activity because this is correlated with carrying out God's commands and religious values . In every sharia transaction, the contract agreement is made by the parties to be implemented/fulfilled together, not to be violated or ignored, because the contract agreement has a binding nature for the parties agreeing. Hence, the contract is a powerful tool and has an urgent position in every sharia transaction. The contract must be fulfilled and maintained as a joint commitment, and the contract is the primary reference in the event of a dispute. The dharuriyyah element in a sharia transaction can be found in Islamic values that must appear in every contract carried out by each individual; this shows the implementation of hifz al-din because carrying out religious orders related to a contract. So with the description above, the values of Islamic teachings contained in a contract or transaction that must be implemented are a form of maqashid al-shari'ah that must exist in the practice of muamalah.